HIGH SENSITIVITY TROPONIN T: AN AUDIT OF IMPLEMENTATION OF ITS PROTOCOL IN A DISTRICT GENERAL HOSPITAL - Kalim, Shahid; Nazir, Shaista; Khan, Zia Ullah (Journal of Ayub Medical College Abbottabad, 2013)
Background: Protocols based on newer high sensitivity Troponin T (hsTropT) assays can rule in a suspected Acute Myocardial Infarction (AMI) as early as 3 hours. We conducted this study to audit adherence to our Trust's newly introduced AMI diagnostic protocol based on paired hsTropT testing at 0 and 3 hours. Methods: We retrospectively reviewed data of all patients who had hsTropT test done between 1st and 7th May 2012. Patient's demographics, utility of single or paired samples, time interval between paired samples, patient's presenting symptoms and ECG findings were noted and their means, medians, Standard deviations and proportions were calculated. Results: A total of 66 patients had hsTropT test done during this period. Mean age was 63.30±17.46 years and 38 (57.57%) were males. Twenty-four (36.36%) patients had only single, rather than protocol recommended paired hsTropT samples, taken. Among the 42 (63.63%) patients with paired samples, the mean time interval was found to be 4.41±5.7 hours. Contrary to the recommendations, 15 (22.73%) had a very long whereas 2 (3.03%) had a very short time interval between two samples. A subgroup analysis of patients with single samples, found only 2 (3.03%) patient with ST-segment elevation, appropriate for single testing. Conclusion: Our study confirmed that in a large number of patients the protocol for paired sampling or a recommended time interval of 3 hours between 2 samples was not being followed. Keywords: Myocardial Infarction, Troponin T, chest pain, Arrhythmias, Cardiac